Investigation of the effect of insertional mutation in agr and sigB loci in Clostridium difficile R20291 - Montfort-Gardeazabal, Jorge M. (2017)
Clostridium difficile has become the major cause of healthcare acquired diarrhoea in the world. The disease caused by this pathogen is largely mediated by the production of toxins. The C. difficile genome contains an incomplete accessory gene regulator (agr) locus, designated agr1. In Staphylococcus aureus, it has been shown that the agr locus regulates virulence factors through Quorum Sensing (QS). In addition to the incomplete agr1 locus found in all of the C. difficile strains sequenced to date, the strains belonging to the BI/NAP1/027 group possess an additional agr operon, designated agr2. These strains have been found to produce higher toxin levels and a more severe disease in patients. The studies described in this thesis have shown that the two agr systems present in the Clostridium difficile BI/NAP1/027 strain R20291 are involved in the regulation of spore formation and toxin production. The agr1 locus (agrB1, agrD1) is responsible for the production of the autoinducing peptide (AIP) AgrD1, while the second agr2 locus (agrC, agrA, agrB2, agrD2) mediates production of the AgrD2. Initial mutational analysis using a University of Nottingham isolate (R20291 NM) suggested that AgrD1 both positively regulates sporulation and negatively regulates toxin production, whereas AgrD2 positively regulates toxin production, but negatively regulates spore formation.